Livestock feeding systems - Technical Centre for Agricultural and Rural Cooperation; Caribbean Agricultural Research and Development Institute (Technical Centre for Agricultural and Rural Cooperation, 1990)
Livestock feeding systems for the Caribbean, using non-conventional feed resources